Dry-method electrode, preparation method thereof and battery
By combining polytetrafluoroethylene and ionic polymer in the dry electrode and adopting high-temperature multi-stage rolling technology, the problem of polytetrafluoroethylene embedded lithium at low voltage is solved, the cycle performance and adhesion of the battery are improved, and more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202311438348.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
Among the existing dry electrodes, polytetrafluoroethylene is prone to be embedded with lithium at low voltage as a binder, resulting in a decrease in the battery's first effect and a lower adhesion force.
The first binder polytetrafluoroethylene and the second binder ionic polymer are added simultaneously to the dry electrode. Through high-temperature multi-stage rolling technology, polytetrafluoroethylene fibrosis under the action of shear force to form a network-like structure, while the ionic polymer achieves in-situ crosslinking at high temperatures, improving bonding performance and interface contact.
Improves the cycling performance of the battery, enhances the adhesion strength and adhesion of the electrodes, avoids solvent residues, and reduces equipment investment and energy consumption.
Smart Images

Figure CN119920818A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a dry electrode and a preparation method thereof, and a battery. Background Art
[0002] The production of electrode plates is the primary link in the manufacture of battery cells and is one of the factors that affect the basic performance of battery cells. At present, most electrode plates are prepared by wet coating. This preparation method is not only complicated, but the volatilization of solvents during the preparation process is easy to cause environmental pollution. In addition, the wet stirring coating process is prone to gelation, coating cracking, and adhesive floating. In addition, there is also the problem of solvent residue in the coated electrode. In the preparation process of electrode plates, in order to recover the solvent well, the equipment capacity requirements will be relatively high, and this will also increase the process cost.
[0003] As a new production process for lithium-ion batteries, dry electrode technology has the following advantages over conventional wet electrodes: the process is simple, there is no problem of solvent volatilization, and equipment investment and energy consumption are significantly reduced; at the same time, under high temperature, electrolyte and other conditions, dry electrodes prepared by the dry process have better bonding properties and adhesion, which can further improve the overall performance of the battery.
[0004] The existing dry processes are mainly adhesive fibrillation and electrostatic spraying. The electrostatic spraying method is not as good as the adhesive fibrillation method in terms of processability, adhesion stability, electrode flexibility and durability. The adhesive fibrillation method is a process in which the fiberized adhesive is mixed with the active electrode material and drawn into a ball, then hot-pressed into a film, and finally thermally compounded with the current collector. The most common binder at present is polytetrafluoroethylene (PTFE), but PTFE is easily embedded with lithium at low voltage, resulting in a reduction in the first effect, and the bonding and cohesive forces of the PTFE-based binder electrode are relatively low.
[0005] Therefore, it is necessary to provide a dry electrode and a preparation method thereof and a battery to solve the above problems. Summary of the invention
[0006] In view of the above shortcomings of the prior art, the present invention provides a dry electrode and a preparation method thereof and a battery to improve the problem of reduced initial efficiency and low bonding force of the dry electrode due to lithium insertion of the binder polytetrafluoroethylene under low pressure.
[0007] To achieve the above-mentioned purpose and other related purposes, the present invention provides a dry electrode on the one hand, which includes: a current collector and a dry electrode membrane arranged on at least one side surface of the current collector, wherein the dry electrode membrane includes an active material, a conductive agent, a first binder and a second binder, the first binder includes polytetrafluoroethylene, and the second binder is selected from an ionic polymer.
[0008] In one example of the present invention, the second binder is selected from at least one of the compounds represented by formula (1), formula (3) and formula (7):
[0009]
[0010] In formula (1), the value range of x1 is 1500 to 3000, the value range of y1 is 1400 to 2800, and the structural formula of R1 is shown in formula (2):
[0011]
[0012] The value range of a in formula (2) is 1 to 3;
[0013]
[0014] In formula (3), the value range of x2 is 1000-2000, the value range of y2 is 1000-2300, the value range of b is 4-8, and R2 is selected from any one of formulas (4) to (6):
[0015]
[0016] The value range of c in formula (4) is 1 to 3; the value range of d in formula (6) is 1 to 4;
[0017]
[0018] In formula (7), the value range of x3 is 900~1700; the value range of y3 is 800~1600; the value range of z is 900~1900; the value range of e is 4~8.
[0019] In one example of the present invention, the dry electrode is a positive electrode sheet. Based on the total mass of the dry electrode film, the content of the active material is 91.0-98.6wt%, the content of the conductive agent is 0.4-5wt%, the content of the first binder is 0.2-1wt%, and the content of the second binder is 0.8-3wt%.
[0020] In one example of the present invention, the dry electrode is a negative electrode plate. Based on the total mass of the dry electrode film, the content of the active material is 91.7-98.5wt%, the content of the conductive agent is 0.2-5wt%, the content of the first binder is 0.1-0.3wt%, and the content of the second binder is 1.2-5wt%.
[0021] On the other hand, the present invention provides a method for preparing a dry electrode, which includes: a dry powder mixing step, in which the active material, the conductive agent, the first binder and the second binder are evenly mixed to obtain a first mixture; a fiberization step, in which the first mixture is fiberized under shearing action to obtain a second mixture; a film forming step, in which the second mixture is extruded and formed to obtain a dry electrode film; and a composite step, in which the dry electrode film is rolled and thinned, and composited with a current collector to obtain a dry electrode.
[0022] In an example of the present invention, the dry powder mixing step includes: mixing the active material, the conductive agent, the first binder and the second binder at a temperature of -40 to 0° C. for 15 to 30 minutes.
[0023] In one example of the present invention, the fiberization step includes: pre-fiberizing the first mixture at 60-120° C. for 30 minutes, and then dispersing the first mixture under the action of shear force for 15-60 minutes.
[0024] In one example of the present invention, the film forming step includes: mixing and conveying the second mixed material through a screw and extruding it through a die to form a dry electrode film, wherein the temperature of the screw is 120-160°C and the thickness of the dry electrode film is 2-7 μm.
[0025] In one example of the present invention, the composite step includes: thinning the dry electrode film to 0.5-2 mm by rolling, and then hot rolling composite it with the collector to form a dry electrode, wherein the rolling pressure of the hot rolling composite is 3-50T and the rolling temperature is 80-160°C.
[0026] The present invention also provides a battery, comprising the dry electrode described above.
[0027] In the present invention, a first binder polytetrafluoroethylene and a second binder are simultaneously added to the dry electrode, wherein polytetrafluoroethylene as a binder is fibrous under the action of shear force to form a network structure for bonding the active material and the conductive agent; the second binder is selected from an ionic polymer, and the ionic polymer is in-situ cross-linked while the mixed material is mixed and extruded at high temperature to form a film, so that the ionic polymer is more evenly distributed in the electrode, promoting Li + transmission, ensuring good interface contact; Li + Electrostatic coupling between the sulfonate terminal and the quaternary ammonium cation facilitates the Li + The self-healing function of the dynamic cross-linked network binder composed of hydrogen bonds and electrostatic interactions can repair cracks in the electrode and maintain structural integrity during long-term cycling, thereby improving the cycling performance of the battery.
[0028] The present invention adopts a dry process without using solvents, which can avoid solvent residues in the electrode and reduce equipment investment, energy consumption and costs. At the same time, high-temperature multi-stage rolling is adopted to improve the consistency of the electrode sheet, and thicker electrode sheets can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A schematic diagram of the structure of a dry electrode according to an embodiment of the present invention;
[0031] Figure 2 A flow chart of a method for preparing a dry electrode according to an embodiment of the present invention;
[0032] Figure 3 A schematic diagram of a method for preparing a dry electrode of the present invention using single-screw extrusion film forming and roller pressing composite in one embodiment;
[0033] Figure 4 A schematic diagram of a method for preparing a dry electrode of the present invention using twin-screw extrusion film forming and roller pressing composite in one embodiment;
[0034] Figure 5 A schematic diagram of a method for preparing a dry electrode of the present invention using a four-roller mode roll-compression composite in one embodiment;
[0035] Figure 6 It is a schematic diagram of the extrusion film forming, thinning and compounding in one embodiment of the preparation method of the dry electrode of the present invention.
[0036] Reference numerals
[0037] 10. Dry electrode; 11. Current collector; 12. Dry electrode membrane; 20. Single-screw extruder; 21. Die head; 12. Dry electrode membrane; 30. Winding mechanism; 40. Unwinding mechanism; 50. Compounding mechanism; 60. Twin-screw extruder; 70. Pair of rollers. DETAILED DESCRIPTION
[0038] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0040] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0041] In this document, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0042] Herein, "preferred", "better" and "more preferred" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0043] Herein, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0044] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0045] See also Figure 1In one aspect, the present invention provides a dry electrode, the dry electrode 10 comprising a current collector 11 and a dry electrode film 12, wherein the dry electrode film 12 is disposed on at least one side of the current collector 11, that is, the current collector 11 has two oppositely disposed first and second surfaces along the thickness direction, the dry electrode film 12 can be disposed on any one of the first and second surfaces, or on both the first and second surfaces. The dry electrode film 12 comprises an active material, a conductive agent, a first binder and a second binder, the first binder comprises polytetrafluoroethylene, and the second binder is selected from ionic compounds.
[0046] See also Figure 1 The material of the current collector 11 can be selected according to the type of the dry electrode 10. For example, if the dry electrode is a positive electrode sheet, the current collector 11 can be made of aluminum foil with a thickness of 5 to 20 μm. Furthermore, the thickness of the aluminum foil is 10 to 15 μm. Furthermore, the thickness of the aluminum foil is 12 μm. The current collector 11 can also be made of a composite current collector. The composite current collector uses a polymer insulating resin material as a "sandwich" layer, and aluminum is deposited on its upper and lower surfaces. The polymer resin can be polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, polyamide PA, etc. If the electrode is a negative electrode, the current collector 11 can be a copper foil with a thickness of 4 to 15 μm, further, the thickness of the copper foil is 5 to 10 μm, and further, the thickness of the copper foil is 8 μm; the current collector 11 can also be a composite current collector, which uses a polymer insulating resin material as a "sandwich" layer, with copper deposited on the upper and lower surfaces. The polymer resin can be selected from polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, polyamide PA, etc.
[0047] See also Figure 1 The active material in the dry electrode film 12 is the main substance involved in the electrochemical reaction. The selection of the active material is related to the battery type and the type of the dry electrode 10. Taking a lithium-ion battery as an example, when the dry electrode is a positive electrode sheet, the active material is selected from one or more of lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), ternary materials, lithium-rich materials, polyanion materials, and lithium-sulfur positive electrode materials. Among them, the ternary materials include but are not limited to LiNi 0.5 Mn 1.5 O4、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNiCoAlO2; polyanion materials such as lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4) or polyanion positive electrode materials such as borates and sulfates. That is, the active material can be any one of the materials listed above, or a combination of any two or more, without limitation here. Of course, the active material can also be a positive electrode material not listed above. When the dry electrode 10 is a negative electrode sheet, the active material is selected from one or more mixtures of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, silicon, silicon oxide, silicon-carbon composite material, silicon / germanium composite material, lithium titanate, and lithium. For example, the active material is artificial graphite, or a mixture of artificial graphite and silicon, and so on. When the active material is a composition of two or more materials, there is no limitation on the ratio between the components in the composition, and they can be mixed in any proportion.
[0048] The conductive agent in the dry electrode film 12 can improve the electronic conductivity. In order to ensure that the battery has good charge and discharge performance, it plays the role of collecting microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the battery and accelerate the movement rate of electrons. In addition, the conductive agent can also improve the processability of the electrode, promote the infiltration of the electrolyte into the electrode, and effectively improve the migration rate of lithium ions in the battery material, thereby improving the charge and discharge efficiency of the battery and the service life of the battery. The conductive agent includes but is not limited to carbon black, acetylene black, carbon nanotubes, carbon fiber, graphene, Ketjen black. The conductive agent can be any one of the materials listed above, or a combination of any two or more of the materials listed above. For example, the conductive agent is carbon black; or carbon nanotubes; or a combination of carbon black and acetylene black; or a combination of carbon fiber, acetylene black and graphene, and so on. It should be noted that when the conductive agent is a plurality of compositions, there is no restriction on the ratio between the components in the composition, and any proportion can be mixed.
[0049] The binder in the dry electrode membrane 12 is used to bond the active material and the conductive agent. The inventors found in their research that polytetrafluoroethylene is easily embedded with lithium at low voltage, resulting in a decrease in the first efficiency of the battery and low bonding force. Therefore, the binder of the present invention includes a first binder and a second binder, wherein the first binder includes polytetrafluoroethylene (PTFE), and polytetrafluoroethylene is fiberized under the action of high shear force to form a rich fiber network between the active material and the conductive agent. The molecular weight of polytetrafluoroethylene in the present invention is 60W to 120W, for example, 60W, 80W, 700W or 120W, and the relative standard density (SSG) is 2.1 to 2.3, for example, 2.1, 2.2 or 2.3, etc. In other embodiments, the first binder can also be carboxymethyl cellulose (CMC) or polyvinylidene fluoride (PVDF), etc. The second binder is selected from an ionic polymer, which can be in-situ cross-linked at high temperature, so that the ionic polymer is more evenly distributed in the dry electrode membrane 12, promoting Li + transmission, ensuring good interface contact; secondly, the sulfonate ions and quaternary ammonium cations in the ionic polymer and Li + The electrostatic coupling between them is beneficial to promote the + The self-healing function of the dynamic cross-linked network binder composed of hydrogen bonds and electrostatic interactions can repair cracks in the electrode and maintain structural integrity during long-term cycling, thereby improving the cycling performance of the battery.
[0050] In some embodiments, the second binder may be selected from any one of the compounds represented by the following structural formula (1), structural formula (3) and structural formula (7), or a combination of any two or more thereof:
[0051]
[0052] In formula (1), the value range of x1 is 1500-3000, that is, x1 can select any value within the above range, for example, x1 can be 1500, 2000, 2500 or 3000, etc.; the value range of y1 is 1400-2800, that is, y1 can be any value within the above range, for example, y1 can be 1400, 2000, 2500 or 2800, etc.; the structural formula of R1 is shown in formula (2):
[0053]
[0054] The value range of a in formula (2) is 1 to 3, for example, a is 1, or 2, or 3, etc.
[0055] The second binder represented by formula (1) can be prepared by conventional methods in the art, for example: CF2=CF2 and CF2=CFR1 are mixed in a certain molar ratio, and a polymerization reaction is carried out under the conditions of 50-140°C and 2-6MPa through the action of an initiator and a catalyst to form the above-mentioned binder, wherein the molar ratio of CF2=CF2 and CF2=CFR1 can be 1:1, the initiator can be selected from perfluoroalkyl sulfonates, the catalyst can be ammonium persulfate, and the specific reaction temperature and reaction pressure can be selected within the above-mentioned range, for example, the reaction temperature can be 50°C, 80°C, 100°C, 140°C, etc., and the reaction pressure can be 2MPa, 4MPa or 6MPa, etc.
[0056]
[0057] In formula (3), the value range of x2 is 1000-2000, further, the value range of x2 is 1300-1700, further, x2 can be 1500; the value range of y2 is 1000-2300, further, the value range of y2 is 1500-2000, further, y2 can be 1800; the value range of b is 4-8, further, b can be 4, 6 or 8, etc. R2 is selected from any one of formulas (4) to (6):
[0058]
[0059] In formula (4), the value range of c is 1 to 3. For example, c can be 1, 2 or 3;
[0060]
[0061] In formula (6), the value range of d is 1 to 4. For example, d can be 1, 2, 3 or 4.
[0062] The second binder represented by formula (3) can be prepared by conventional methods in the art, for example, by converting CH2=CHCOO(CH2CH2O) b Mixed with CH2=CHR2 in a certain molar ratio, the above-mentioned binder is synthesized by catalysis of tert-butyl peroxide at 120-180°C and 15-25MPa. b The molar ratio with CH2=CHR2 can be 1:1, and the reaction temperature and pressure can be any value within the above-listed ranges, for example, the reaction temperature can be 120°C, 150°C or 180°C, etc.; the reaction pressure can be 15MPa, 20MPa or 25MPa, etc. The R2 group in formula (3) is the same as R2 in the reactant CH2=CHR2.
[0063]
[0064] In formula (7), the value range of x3 is 900-1700, and further, the value range of x3 is 1000-1500, for example, 1200 or 1400; the value range of y3 is 800-1600, and further, the value range of y3 is 1000-1500, for example, 1200, 1300 or 1500; the value range of z is 900-1900, and further, the value range of z is 1200-1700, and further, Z can be 1400 or 1600; the value range of e is 4-8, for example, e can be 4, 6 or 8.
[0065] The second binder represented by formula (7) can be prepared by conventional methods in the art. For example, CH2=CHCOO(CH2CH2O) e , CH2=CHCOOCH2CH2OH and CH2=CHCOOCH2CH2N + (CH3)2CH2CH2CH2SO3Li are mixed in a certain molar ratio and synthesized by tert-butyl peroxide at 130-200°C and 25-30MPa, wherein the molar ratio of the above reactants is 1:1:1, and the reaction temperature and reaction pressure can be selected from any values within the above range, for example, the reaction temperature can be 130°C, 150°C, 180°C or 200°C, etc.; the reaction pressure can be 25MPa, 28MPa or 300MPa, etc.
[0066] The ratio of the active material, the conductive agent, the first binder and the second binder in the above-mentioned dry electrode is related to the type of dry electrode. When the dry electrode is a positive electrode sheet, based on the total mass of the dry electrode film, the mass proportion of the active material in the dry electrode film is 91.0-98.6wt%, for example, 93wt%, 95wt%, 98wt%, etc.; the mass proportion of the conductive agent in the dry electrode film is 0.4-5wt%, for example, 0.4wt%, 1wt%, 3wt% or 5wt%, etc.; the mass proportion of the first binder in the dry electrode film is 0.2-1wt%, for example, 0.2wt%, 0.5wt%, 0.8wt% or 1wt%; the mass proportion of the second binder in the dry electrode film is 0.8-3wt%, for example, 0.8wt%, 1wt%, 2wt% or 3wt%, etc. When the dry electrode is a negative electrode sheet, based on the total mass of the dry electrode film, the mass proportion of the active material in the dry electrode film is 91.7-98.5wt%, for example, 91.7wt%, 93wt%, 95wt% or 98.5wt%; the mass proportion of the conductive agent in the dry electrode film is 0.2-5wt%, for example, 0.2wt%, 2wt%, 3wt% or 5wt%; the mass proportion of the first binder in the dry electrode film is 0.1-0.3wt%, for example, 0.1wt%, 0.2wt% or 0.3wt%; the mass proportion of the second binder in the dry electrode film is 1.2-5wt%, for example, 1.2wt%, 2wt%, 3wt% or 5wt%.
[0067] See also Figure 1 and Figure 2 On the other hand, the present invention provides a method for preparing the above-mentioned dry electrode, which at least comprises the following steps:
[0068] S1, a dry powder mixing step, mixing the active material, the conductive agent, the first binder and the second binder uniformly to obtain a first mixed material;
[0069] S2, a fiberization step, performing a fiberization treatment on the first mixture under the action of a shear force to obtain a second mixture;
[0070] S3, a film forming step, extruding the second mixed material to form a dry electrode film 12;
[0071] S4, a compounding step, hot rolling-compounding the dry electrode film 12 and the current collector 11 to obtain a dry electrode sheet 10.
[0072] See also Figure 2, the material types of active material, conductive agent, first binder and second binder in step S1 are related to the battery type and electrode type, please refer to the detailed description above. The ratio between the components is related to the electrode type: when the dry electrode is a positive electrode sheet, the mass proportion of active material in the dry electrode film is 91.0-98.6wt%, the mass proportion of conductive agent in the dry electrode film is 0.4-5wt%, the mass proportion of first binder in the dry electrode film is 0.2-1wt%, and the mass proportion of second binder in the dry electrode film is 0.8-3wt%; when the dry electrode is a negative electrode sheet, the mass proportion of active material in the dry electrode film is 91.7-98.5wt%, the mass proportion of conductive agent in the dry electrode film is 0.2-5wt%, the mass proportion of first binder in the dry electrode film is 0.1-0.3wt%, and the mass proportion of second binder in the dry electrode film is 1.2-5wt%. The specific ratio can be selected within the above range according to actual needs.
[0073] Step S1 is to mix the above-mentioned active material, conductive agent, first binder and second binder evenly according to a certain ratio. The specific mixing method is not limited here, and it can be any method in the art that can mix the components evenly. As an example: the active material, conductive agent, first binder and second binder are placed in a premixing device, such as a high-speed disperser, according to a certain ratio, and premixed for 15 to 30 minutes at a low temperature of -40°C to 0°C to fully disperse them. The premixing temperature and premixing time can select any value within the above range. For example, the premixing temperature can be -40°C, -20°C or 0°C, and the premixing time can be 15min, 20min, 25min or 30min. Mixing under low temperature conditions can effectively inhibit the premature fiberization of polytetrafluoroethylene, and at low temperature and high speed, the fine binder powder can fully contact with the active material and conductive agent, and the mixing is more uniform.
[0074] See also Figure 2 , step S2 is to perform a fiberization treatment on the first mixture obtained in step S1 under high shear force, so that the first binder forms a rich fiber network between the active material and the conductive agent, significantly improving the adhesion strength of the dry film. The specific process of fiberization is as follows: first, the first mixture obtained in step S1 is pre-fiberized at 60-120°C for 30 minutes to soften and loosen the polytetrafluoroethylene binder, which is conducive to the subsequent fiberization treatment, and then dispersed at high speed for 15-60 minutes to allow the polytetrafluoroethylene to be fiberized under the action of shear force to form a rich network structure. Among them, the pre-fiberization temperature can be 60°C, 80°C, 100°C or 120°C, etc., and the fiberization treatment time can be 15min, 25min, 40min or 60min, etc.
[0075] See also Figure 2 , Figure 3 and Figure 4 , step S3 extrude the second mixed material obtained in step S2 to obtain a dry electrode membrane. Specifically, the second mixed material is placed in a screw extruder, mixed and conveyed by the screw, and extruded by the die to form a dry electrode membrane 12. Among them, the screw extruder can be a single-screw extruder 20 or a twin-screw extruder 60, and the die 11 of the screw extruder can be a hanger type or a plunger type, which is not limited here. The extrusion temperature of the screw is 120 to 160°C, for example, 120°C, 140°C or 160°C. The second mixed material is mixed and extruded at this temperature, and the second binder is cross-linked in situ, so that the second binder is more evenly distributed in the electrode, promoting Li + transmission, ensuring good interface contact; at the same time Li + Electrostatic coupling between the sulfonate terminal and the quaternary ammonium cation in the second binder is beneficial to promote the Li + The conduction of the electrode and the self-healing function of the dynamic cross-linked network binder composed of hydrogen bonds and electrostatic interactions can repair cracks in the electrode and maintain structural integrity during long-term cycles. The thickness of the extruded dry electrode film 12 is 2 to 7 mm, such as 2 mm, 5 mm or 7 mm, etc.
[0076] See also Figures 2 to 4 In step S4, the dry electrode film 12 prepared in step S3 is compounded with the current collector 11 to form a dry electrode 10. The material of the current collector is related to the type of the dry electrode. When the dry electrode is a positive electrode sheet, the current collector 11 can be made of aluminum foil with a thickness of 5 to 20 μm, further, the thickness of the aluminum foil is 10 to 15 μm, and further, the thickness of the aluminum foil is 12 μm; the current collector 11 can also be made of a composite current collector, which uses a polymer insulating resin material as a "sandwich" layer, and deposits aluminum on its upper and lower surfaces. The polymer resin can be polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, and polyamide PA. When the dry electrode is a negative electrode, the current collector 11 can be a copper foil with a thickness of 4 to 15 μm, further, the thickness of the copper foil is 5 to 10 μm, and further, the thickness of the copper foil is 8 μm; the current collector 11 can also be a composite current collector, which uses a polymer insulating resin material as a "sandwich" layer, with copper deposited on the upper and lower surfaces. The polymer resin can be polyethylene terephthalate PET, polypropylene PP, polyimide PI, polystyrene PS, polyamide PA, etc.
[0077] See also Figures 2 to 6The specific compounding step S4 is as follows: the extruded dry electrode film 12 is transported to the compounding mechanism 50, and at the same time, the unwinding mechanism 40 transports the current collector 11 into the compounding mechanism 50, and the dry electrode film 12 and the current collector 11 are rolled and compounded together by the compounding mechanism 50 to form the dry electrode 10, and then collected and stored by the winding mechanism 30. The above-mentioned composite structure 50 can be a three-roller mode roller press or a four-roller mode roller press, wherein the roller speed ratio in the three-roller mode is A:B:C=1:1:1.5~1:2.5:5.5, for example, it can be 1:1:1.5, 1:1.5:3.5 or 1:2.5:5.5, etc.; the roller speed ratio in the four-roller mode is A:B:C:D=1:1:1:1.5~1:2.5:2.5:5, for example, it can be 1:1:1:1.5, 1:1.5:1.5:3, or 1:2.5:2.5:5, etc. The rolling pressure can be any value between 3 and 50T, such as 3T, 10T, 30T or 50T, and the rolling temperature can be any value within the range of 80 to 160°C, such as 80°C, 120°C or 160°C; preferably, before rolling compounding, the dry electrode film 12 can be thinned to 0.5 to 2 mm, such as 0.5 mm, 1 mm, 1.5 mm or 2 mm, by using a pair of rollers 70, and then hot-rolled compounded with the collector 11 to form a dry electrode 10.
[0078] The present invention also provides a battery, which includes a positive electrode sheet, a negative electrode sheet, a diaphragm and an electrolyte, wherein the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet to play an isolation role; the electrolyte infiltrates the positive electrode sheet and the negative electrode sheet in the shell to play a role in conducting lithium ions; the positive electrode sheet and / or the negative electrode sheet is the dry electrode described above in the present invention, or is prepared by the preparation method described above in the present invention.
[0079] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0080] Example 1
[0081] Positive electrode preparation: The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2O2: SP: first binder PTFE: second binder in a mass ratio of 96.0%: 2.0%: 0.5%: 1.5% premixed at -10°C for 20 minutes, then kept at 80°C for 30 minutes and dispersed at high speed for 30 minutes, extruded at 100°C by a single screw extruder to form a 5mm dry electrode film, and then thinned and compounded to form a positive electrode sheet. Among them, the current collector uses 12μm aluminum foil.
[0082] Negative electrode preparation: The negative electrode active material artificial graphite: SP: first binder PTFE: second binder is premixed at a mass ratio of 97.45%: 0.4%: 0.15%: 2% at -10°C for 20 minutes, then kept at 80°C for 30 minutes and dispersed at high speed for 30 minutes, extruded at 100°C by a single screw extruder to form a 6mm dry electrode film, and then thinned and compounded to form a negative electrode sheet. Among them, 8μm copper foil is used as the current collector.
[0083] Cell preparation: The positive and negative electrode sheets are rolled and die-cut, and then wound, packaged, liquid-filled, and chemically processed to complete the cell preparation.
[0084] The structural formula of the second binder in the positive and negative electrode sheets is as follows:
[0085]
[0086] Where x is 2250 and y is 2100.
[0087] Example 2
[0088] The difference between this embodiment and embodiment 1 is that the second binder in the positive and negative electrode sheets is replaced with a compound shown in the following structural formula:
[0089]
[0090] Where x is 1500 and y is 1500.
[0091] Example 3
[0092] The difference between this embodiment and embodiment 1 is that the second binder in the positive and negative electrode sheets is replaced with a compound shown in the following structural formula:
[0093]
[0094] Here x is 1500 and y is 1905.
[0095] Example 4
[0096] The difference between this embodiment and embodiment 1 is that the second binder in the positive and negative electrode sheets is replaced with a compound shown in the following structural formula:
[0097]
[0098] Here x is 1500 and y is 1283.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 1 is that the second binder in the positive and negative electrode sheets is replaced with a compound shown in the following structural formula:
[0101]
[0102] In the formula, x is 1250, y is 1100, z is 1150, and e is 5.
[0103] Example 6
[0104] The difference between this embodiment and embodiment 1 is that the proportion of each material in the positive electrode plate is adjusted to: LiNi 0.6 Co 0.2 Mn 0.2 O2:SP:first binder PTFE:second binder=95%:2.0%:0.5%:2.5%.
[0105] Example 7
[0106] The difference between this embodiment and embodiment 1 is that the proportion of each material in the positive electrode plate is adjusted to: LiNi 0.6 Co 0.2 Mn 0.2 O2:SP:first binder PTFE:second binder=96%:2.0%:1%:1%.
[0107] Example 8
[0108] The difference between this embodiment and embodiment 1 is that the ratio of the substances in the negative electrode plate is adjusted to: artificial graphite: SP: first binder PTFE: second binder = 96.45%: 0.4%: 0.15%: 3%.
[0109] Example 9
[0110] The difference between this embodiment and embodiment 1 is that the ratio of each substance in the negative electrode plate is adjusted to: artificial graphite: SP: first binder PTFE: second binder = 97.8%: 0.4%: 0.3%: 1.5%.
[0111] Comparative Example 1
[0112] Positive electrode preparation: The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2O2: CNT: SP: binder PVDF: dispersant PVP are evenly dispersed in a mass ratio of 96.9%: 0.8%: 1.0%: 1.0%: 0.3%, wherein the solvent is NMP and the solid content is 75%. They are coated on the current collector and then dried, rolled and cut to form the positive electrode sheet.
[0113] Negative electrode preparation: The negative electrode active material artificial graphite: SP: thickener CMC: binder SBR are evenly dispersed in a mass ratio of 97.1%: 0.4%: 1.0%: 1.5%, wherein the solvent is water and the solid content is 55%, and coated on the current collector and dried, rolled and cut to form a positive electrode sheet.
[0114] After the positive and negative pole pieces are rolled and die-cut, the battery cell is prepared through processes such as winding, packaging, liquid injection and chemical formation.
[0115] Comparative Example 2:
[0116] Cathode active material LiNi 0.6 Co 0.2 Mn 0.2 O2:SP: binder PTFE are mixed in a mass ratio of 95.5%:2.0%:2.5% to form fibers, and then thinned and compounded by roller pressing to form a positive electrode sheet.
[0117] The negative electrode active material artificial graphite: SP: binder PTFE are mixed in a mass ratio of 97.1%: 0.4%: 2.5% to form fibers, and then thinned and compounded by roller pressing to form a negative electrode sheet.
[0118] After the positive and negative pole pieces are rolled and die-cut, the battery cell is prepared through processes such as winding, packaging, liquid injection and chemical formation.
[0119] The pole pieces and cells prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to performance tests. The test methods are shown below. The test results are shown in Table 1.
[0120] (1) Adhesion test:
[0121] The prepared electrode is cut into 20*100mm, and the side to be tested is glued to the stainless steel plate with double-sided tape and compacted with a roller to make it fit completely with the electrode. One end of the stainless steel plate is fixed to the lower fixture of the tensile machine, and the bent end of the sample is fixed to the upper fixture. The tensile speed is 50mm / min.
[0122] (2) Ratio test:
[0123] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C0, charge it with 1 / 3C0 with constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C1, charge it with 1 / 3C0 with constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 3C to 3V, let it sit for 30min, record the discharge capacity Cn, and the 3C capacity retention rate is Cn / C1*100%.
[0124] (3) DCR (DC resistance) test:
[0125] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, let it sit for 30min, discharge it with 1 / 3C0 to 3V, let it sit for 30min, record the discharge capacity C0, charge it with 1 / 3C0 constant current to 4.2V, charge it with constant voltage to 0.05C0, let it sit for 30min, discharge it with 1 / 3C0 for 180min, let it sit for 10min, record the end voltage V0, discharge it with 2C for 30s, record the end voltage V1, discharge DCR = (V0-V1) / I.
[0126] (4) Initial effect and cycle testing:
[0127] Charge the cell with 1 / 3C constant current to 4.2V, charge it with constant voltage to 0.05C, record the charging capacity C0, let it sit for 30 minutes, discharge it with 1 / 3C0 to 3V, let it sit for 30 minutes, record the discharge capacity D0, charge it with 1 / 3D0 with constant current to 4.2V, charge it with constant voltage to 0.05D0, let it sit for 30 minutes, discharge it with 1 / 3D0 to 3V, let it sit for 30 minutes, record the discharge capacity D1, and record the discharge capacity Dn at the end of each cycle in this way. The cycle capacity retention rate is Dn / D1*100%, record the number of cycles N when the retention rate is 80%, and the first efficiency is D0 / C0*100%.
[0128] Table 1: Performance comparison of dry-process electrodes and cells prepared in Examples 1 to 9 and Comparative Examples 1 to 2
[0129]
[0130]
[0131] Comparison of Examples 1 to 5 and Comparative Examples 1 and 2: In Examples 1 to 5, different types of second binders are added in the same proportion, and the bonding force of the positive electrode sheets prepared therefrom is greatly improved compared with the positive electrode sheets prepared in Comparative Example 2 (without adding the second binder) and Comparative Example 1 (wet process); at the same time, the first efficiency, rate performance, DCR performance and cycle performance of the battery cells assembled in Examples 1 to 5 are improved compared with the battery cells assembled in Comparative Example 2, especially the cycle performance, the improvement is more obvious.
[0132] By comparing Example 1, Example 6 and Example 7, it can be concluded that: within a certain range, increasing the addition ratio of the second binder in the positive electrode plate can improve the bonding strength of the positive electrode plate, and the first efficiency, rate performance, DCR performance and cycle performance of the battery cell will also be improved to a certain extent; when the amount of the second binder added is large, although the bonding strength of the plate is improved, the electrical performance of the battery cell is not significantly improved because the ratio of the active material, the conductive agent and the first bonding agent will also change.
[0133] By comparing Example 1, Example 8 and Example 9, it can be concluded that: within a certain range, increasing the amount of the second binder added in the negative electrode sheet will improve the first efficiency, rate performance, DCR performance and cycle performance of the battery cell to a certain extent; but as the amount of the second binder added increases, the DCR value of the battery cell continues to increase. When the DCR value is large, the first efficiency, capacity retention rate and cycle performance of the battery cell will decrease. Therefore, adding an appropriate amount of the second binder can improve the comprehensive performance of the battery cell.
[0134] In the present invention, a first binder and a second binder are simultaneously added to the dry electrode. Under high temperature insulation and high-speed dispersion, the first binder is fibrotic to form a network structure to bind the active material and the conductive agent. When the mixed material is mixed and extruded at high temperature to form a film, the second binder is cross-linked in situ, so that the ion polymer is more evenly distributed in the electrode, promoting Li + transmission, ensuring good interface contact; Li + Electrostatic coupling between the sulfonate terminal and the quaternary ammonium cation facilitates the Li + The conduction of the electrode and the self-healing function of the dynamic cross-linked network binder composed of hydrogen bonds and electrostatic interactions can repair cracks in the electrode and maintain structural integrity during long cycles, thereby improving the cycle performance of the battery. The dry process of the present invention does not require the use of solvents, which reduces the use of equipment such as ovens during the coating process, thereby reducing energy consumption and plant costs; at the same time, the present invention adopts high-temperature multi-stage rolling to improve the consistency of the pole piece and can prepare thicker pole pieces. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0135] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A dry electrode, characterized in that: include: current collector; A dry electrode membrane is disposed on the surface of at least one side of the current collector; The dry electrode membrane comprises an active material, a conductive agent, a first binder and a second binder, wherein the first binder comprises polytetrafluoroethylene, and the second binder is selected from an ion polymer.
2. The dry electrode according to claim 1, characterized in that: The second binder is selected from at least one of the compounds represented by formula (1), formula (3) and formula (7): In formula (1), the value range of x1 is 1500 to 3000, the value range of y1 is 1400 to 2800, and the structural formula of R1 is shown in formula (2): The value range of a in formula (2) is 1 to 3; In formula (3), the value range of x2 is 1000-2000, the value range of y2 is 1000-2300, the value range of b is 4-8, and R2 is selected from any one of formulas (4) to (6): The value range of c in formula (4) is 1 to 3; the value range of d in formula (6) is 1 to 4; In formula (7), the value range of x3 is 900~1700; the value range of y3 is 800~1600; the value range of z is 900~1900; the value range of e is 4~8.
3. The dry electrode according to claim 1, characterized in that: The dry electrode is a positive electrode sheet. Based on the total mass of the dry electrode film, the content of the active material is 91.0-98.6wt%, the content of the conductive agent is 0.4-5wt%, the content of the first binder is 0.2-1wt%, and the content of the second binder is 0.8-3wt%.
4. The dry electrode according to claim 1, characterized in that: The dry electrode is a negative electrode sheet. Based on the total mass of the dry electrode film, the content of the active material is 91.7-98.5wt%, the content of the conductive agent is 0.2-5wt%, the content of the first binder is 0.1-0.3wt%, and the content of the second binder is 1.2-5wt%.
5. A method for preparing a dry electrode according to any one of claims 1 to 4, characterized in that: include: A dry powder mixing step, in which the active material, the conductive agent, the first binder and the second binder are uniformly mixed to obtain a first mixed material; a fiberizing step of subjecting the first mixture to fiberization under shearing action to obtain a second mixture; A film forming step, extruding the second mixed material to form a dry electrode film; In the compounding step, the dry electrode film is rolled to be thinned and compounded with a current collector to obtain a dry electrode.
6. The preparation method according to claim 5, characterized in that: The dry powder mixing step includes: mixing the active material, the conductive agent, the first binder and the second binder at a temperature of -40 to 0° C. for 15 to 30 minutes.
7. The preparation method according to claim 5, characterized in that: The fiberization step includes: pre-fiberizing the first mixture at 60-120° C. for 30 minutes, and then dispersing it under the action of shear force for 15-60 minutes.
8. The preparation method according to claim 5, characterized in that: The film forming step includes: mixing and conveying the second mixed material through a screw and extruding it through a die to form a dry electrode film, wherein the temperature of the screw is 120-160° C., and the thickness of the dry electrode film is 2-7 μm.
9. The preparation method according to claim 5, characterized in that: The compounding step includes: thinning the dry electrode film to 0.5-2 mm by rolling, and then hot rolling compounding with the current collector to form a dry electrode, wherein the rolling pressure of the hot rolling compound is 3-50T and the rolling temperature is 80-160°C.
10. A battery, characterized in that: It comprises the dry electrode described in any one of claims 1 to 4.
Citation Information
Patent Citations
Adhesive for electrode and preparation method thereof, negative electrode of lithium ion battery, and lithium ion battery
CN110511377A
In-situ preparation method of dry-method electrode membrane and dry-method electrode thereof
CN114171710A
Electrodes including novel binders and methods of making and using the same
WO2008097723A1
Separator for lithium secondary battery, manufacturing method therefor, and lithium secondary battery including same
WO2020235971A1
Multilayer composite positive electrode plate and secondary battery containing same
WO2021238709A1
Cited By
Dry-method positive pole piece as well as preparation method and application thereof
CN120497281A
Layered dry-method silicon-based negative electrode plate, preparation method thereof and battery
CN120878736A